Time‐Resolved Structural Kinetics of an Organic Mixed Ionic–Electronic Conductor. Issue 40 (30th August 2020) - Paulsen, Bryan D.; Wu, Ruiheng; Takacs, Christopher J.; Steinrück, Hans‐Georg; Strzalka, Joseph; Zhang, Qingteng; Toney, Michael F.; Rivnay, Jonathan
Abstract: The structure and packing of organic mixed ionic–electronic conductors have an especially significant effect on transport properties. In operating devices, this structure is not fixed but is responsive to changes in electrochemical potential, ion intercalation, and solvent swelling. Toward this end, the steady‐state and transient structure of the model organic mixed conductor, poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), is characterized using multimodal time‐resolved operando techniques. Steady‐state operando X‐ray scattering reveals a doping‐induced lamellar expansion of 1.6 Å followed by 0.4 Å relaxation at high doping levels. Time‐resolved operando X‐ray scattering reveals asymmetric rates of lamellar structural change during doping and dedoping that do not directly depend on potential or charging transients. Time‐resolved spectroscopy establishes a link between structural transients and the complex kinetics of electronic charge carrier subpopulations, in particular the polaron–bipolaron equilibrium. These findings provide insight into the factors limiting the response time of organic mixed‐conductor‐based devices, and present the first real‐time observation of the structural changes during doping and dedoping of a conjugated polymer system via X‐ray scattering. Abstract : Time‐resolved operando scattering captures the transient microstructural changes of an organic mixed ionic–electronic conductor in response to dynamic electrochemical potential. The timescales of structural changes related to doping and dedoping are not symmetrical. Combined with spectroelectrochemical measurements, the close relationship between microstructure transients and polaron–bipolaron population kinetics is revealed.